Mitochondrial Dysfunction in Early Diagnosed Autism Spectrum Disorder Children - Shahjadi, Shorifa; Khan, Arif Salam; Ahmed, Mesbah Uddin (Journal of Dhaka Medical College, 2017)
Background: Mitochondrial dysfunction and abnormal brain bioenergetics can cause autism.Cellular function impairment due to mitochondrial dysfunction may cause cognitive impairment, language deficits and abnormal energy metabolism in autism. Objective: The aim of this study was to evaluate biochemical evidence of the mitochondrial dysfunction by measuring blood ammonia, serum lactate, alanine aminotransferase (ALT), aspartate aminotransferase (AST) and creatinine kinase (CK) in autism spectrum disorder children. Methods: This observational type of analytical study with case-control design was conducted in the Department of Physiology of Bangabandhu Sheikh Mujib Medical University (BSMMU), Shahbag, Dhaka. For this study, a total number of 20 Subjects were randomly selected, among which 10 were apparently healthy subjects (control group-A) for comparison and 10 were diagnosed children with autism spectrum disorder (study group-B). 5ml venous blood was collected from both groups for analysis serum CK, AST, ALT, lactate and blood ammonia. Blood ammonia, serum lactate, AST, ALT and CK level were estimated in all children by standard laboratory method. Independent samplet test was used for statistical analysis. P value <0.05 was accepted as significant. The mean of all the measured biochemical variables in normal children were within normal ranges. Result: Blood ammonia, serum lactate, AST, CK were found significantly higher in autism spectrum disorder children in comparison to control Conclusion: From the result of this study it may be concluded that mitochondrial dysfunction occur in autistic spectrum disorder children . J Dhaka Medical College, Vol. 26, No.1, April, 2017, Page 43-47